1996
DOI: 10.1016/s0896-6273(00)80101-4
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Somatic and Dendritic Inhibition in the Hippocampus

Abstract: Hippocampal synaptic inhibition is mediated by distinct groups of inhibitory cells. Some contact pyramidal cells perisomatically, while others terminate exclusively on their dendrites. We examined perisomatic and dendritic inhibition by recording from CA3 inhibitory and pyramidal cells and injecting biocytin to visualize both cells in light and electron microscopy. Single perisomatic inhibitory cells made 2-6 terminals clustered around the soma and proximal pyramidal cell processes. Dendritic cells established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
813
3
14

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 887 publications
(860 citation statements)
references
References 37 publications
30
813
3
14
Order By: Relevance
“…In the tissue derived from tumor-induced epileptic tissue (in which the GABA release experiments have been done), we found that almost one-third of the CB1-positive cells were negative for CCK. In contrast, the absolute number and size of the boutons may vary widely across different interneuron types, 12,16,30 which likely correlates with the amount of released GABA, and may also explain the discrepancy between the quantitative data of the anatomical and pharmacological experiments.…”
Section: Cb1 Cannabinoid Receptor Activation Leads To a Reduction Of mentioning
confidence: 99%
“…In the tissue derived from tumor-induced epileptic tissue (in which the GABA release experiments have been done), we found that almost one-third of the CB1-positive cells were negative for CCK. In contrast, the absolute number and size of the boutons may vary widely across different interneuron types, 12,16,30 which likely correlates with the amount of released GABA, and may also explain the discrepancy between the quantitative data of the anatomical and pharmacological experiments.…”
Section: Cb1 Cannabinoid Receptor Activation Leads To a Reduction Of mentioning
confidence: 99%
“…Recently, GABA has also been shown to exert a compartmental modulation of soma and dendrites in single hippocampal pyramidal neurons (Buhl et al 1994; Kim et al 1995;Miles et al 1996). In the dendrites, GABAergic inhibitory postsynaptic potentials (IPSPs) may serve the following functions.…”
Section: Actions Of Gaba Interneurons On Pfc Pyramidal Neuronsmentioning
confidence: 99%
“…The pyramdial neuron receives functionally segregated inputs in its apical dendrites and basal dendrites from diverse cortical and subcortical regions (see Table 1). The GABAergic interneuron exerts tonic hyperpolarizing action in the apical dendrites, as well as in the somatic region of the pyramidal cell (Soltesz et al 1995;Miles et al 1996;Kim et al 1995). The modulatory inputs to the pyramidal dendrite by the GABAergic interneurons can, in turn, be regulated by mesocortical dopamine inputs to these interneurons.…”
Section: Synthesis Of a Neuronal Model Of Schizophrenia Based On The mentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these inhibitory cells forms multiple synaptic contacts that are distributed along various branches of a single pyramidal neuron. This distribution implies that each contact may have only a very weak effect on the postsynaptic neuron, suggesting that the activity of dendritic inhibitory cells may have to be synchronized in order to effectively modulate the membrane potential of pyramidal neurons (Freund and Buzsaki 1996;Miles et al 1996). Another common factor is that the dendritic arborization of these neurons tends to be restricted to only one or two layers so that their influence is limited to selective intrinsic or extrinsic afferents (for a review see Freund and Buzsaki 1996).…”
mentioning
confidence: 99%